SGLT-2 inhibitors reduce glucose absorption from peritoneal dialysis solution by suppressing the activity of SGLT-2 - Ying Zhou (Biomedicine & Pharmacotherapy, 2019)
Background: Sodium glucose cotransporter-2 (SGLT-2) inhibitors have been widely used in the clinic to reduce blood glucose levels by enhancing glucose excretion. However, whether such agents might also reduce glucose absorption via the peritoneal function of human peritoneal mesothelial cells (HPMCs) that also express SGLT-2 is not clear. Methods: An acute peritoneal dialysis (PD) model in nonuremic rats was established. Ratios of peritoneal glucose uptake at D4/D0 of Sprague-Dawley rats treated with the SGLT-2 inhibitor, empagliflozin were tested to evaluate the effect of this inhibitor on peritoneal glucose absorption. An in vitro model of HPMCs obtained from peritoneal dialysate effluent in patients undergoing PD was used. HPMCs were exposed to high glucose (60 mM) in the presence and absence of empagliflozin. Glucose uptake and glucose consumption, which were used to estimate the activity of SGLT-2 in HPMCs, were measured by flow cytometry and hexokinase respectively. The expression of SGLT-2 in both peritoneum and HPMCs was also observed by real-time polymerase chain reaction (PCR), western blot, and immunofluorescence staining. Results: Both ratios of peritoneal glucose uptake at D4/D0 and ultrafiltration of rats treated with 3 mg kg−1 of empagliflozin for 3 days increased significantly compared to those of the control group (0.32 ± 0.40 vs. 0.11 ± 0.11 mM, P = 0.001；17.00 ± 3.58 vs. -13.67 ± 17.25 ml, P = 0.002). Compared to the control group, the expression of mRNA and protein in SGLT-2 increased significantly in the rats treated with 3 mg kg−1 of empagliflozin for 3 days. Both glucose consumption and uptake of HPMCs incubated with 1 μM of empagliflozin for 24 h decreased significantly compared to control values (8.69 ± 1.77 vs. 11.48 ± 1.00 mM, P = 0.004; 31.97 ± 4.81 vs. 43.98 ± 1.38, P =  0.002). Conclusion: An SGLT-2 inhibitor was able to exert a glucose-lowering effect in peritoneum exposed to PD solution by inhibiting the activity of SGLT-2.